If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -5y = -12solvey Solving 3x + -5y = -12elosvy Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5y' to each side of the equation. 3x + -5y + 5y = -12elosvy + 5y Combine like terms: -5y + 5y = 0 3x + 0 = -12elosvy + 5y 3x = -12elosvy + 5y Divide each side by '3'. x = -4elosvy + 1.666666667y Simplifying x = -4elosvy + 1.666666667y
| 10+10c=3c+c | | 3n^2-21=2n | | 22.9+3.00= | | 6x-20=3x+13 | | 2r^2-9r=-7 | | -5-t=21 | | 8=10+3x | | 2(2b+10)=12(b-1) | | 15x+8=20+3x | | 4(2x-2y)+5(2y-x)= | | S=2(3.14159)r^2+2(3.14159)rh | | x^2+6x+10=5 | | 9-9a= | | .75x=20 | | -5+3x=-14 | | (lnx+1)(lnx-1)=0 | | -4(r+8)=-55 | | 8x-2(2x-3)=12+2x | | 7-5v=-4v | | 5(2x+1)-3(x-3)=63 | | x^2+19x+65=0 | | -9(-2w+3x-6)= | | 1=-7x | | 40+9-30+2= | | 15x+2=6x+10 | | 1059/10=18/1(14/13x) | | -1=-7x | | 6.2h-0.4=2.7 | | 3a+18=3(2a+3) | | X^2+12x-43=4x+5 | | -2=-7x | | -4x+6x^2+5x= |